PENERAPAN METODE DECISION TREE C4.5 DAN NAIVE BAYES PADA KLASIFIKASI KARAKTERISTIK KEPRIBADIAN MANUSIA - Muhammad Hendry; Yan Mitha Djaksana (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
An employee's personal character influences a person's attitude and behavior, including his work attitude and behavior. In other words, personality has an influence on employee performance, so it makes sense for a boss or management to first understand the condition or type of employee personality when trying to improve employee performance. At PT. Insan Pratama's vision is to add to the team and employees by conducting interviews and written tests, but these two methods are still not enough to know the personality of prospective employees specifically, so there are still many considerations in selecting new prospective employees. The C4.5 algorithm is one of the machine learning algorithms. By using this algorithm, a machine (computer) will be given a set of data to study, which is called a learning dataset. The Naive Bayes algorithm is one of the statistical classifiers that can predict the probability of data being owned by displaying classes from certain classes based on possible probabilities. This system can produce information on personality characteristics using the Decision Tree C4.5 and Naïve Bayes methods.